Efficacy of two potent soilborne streptomyces spp. In controlling wilt and root rot disease of tomato (lycopersicon esculentum mill) under greenhouse conditions - AHMED I. S. AHMED (International Journal of Pharma and Bio Sciences, 2017)
Seventy two isolates of Actinomycetes were isolated from various new reclaimed areas “North Sinai, South Sinai, Northern Coastal Zone and Siwa Oasis” Egypt, from 2013-2015. All isolates were tested for their antagonistic ability against some plant pathogenic “fungi Alternaria alternata, Alternaria solani, Cladosporium cladosporioides, Curvularia spp., Fusarium oxysporum, Fusarium solani, Fusarium moniliforme, Macrophomina phaseolina, Pythium ultimum, and Rhizoctonia solani” and exhibited different antifungal effects under in vitro culture conditions. Twelve isolates were found to be antagonist against the most of the tested fungi, while two isolates (Act5 and Act11) exhibited antagonistic effect against all tested phytopathogenic fungi, which were identified as Streptomyces spp. The obtained results showed that Act5 inhibited the mycelial growth of the pathogens Rhizoctonia solani and Fusarium oxysporum f.sp. lycopersici by 82, 75% while the inhibition rates were 71, 78%, by Act11. The activities of two isolates of Streptomyces spp. were investigated on tomato plants against Fusarium oxysporum f. sp. lycopersici and Rhizoctonia solani under greenhouse conditions. Act5 reduced disease incidence by 61.1% and 57.3%, when applied before and after artificial soil infestation, while Act11 reduced the diseases incidence by 50.8% and 42.7%, before and after artificial soil infestation, respectively compared with the control. Moreover, Act5 and Act11 have positive effects on different growth traits (shoot/root length, shoot/root fresh weight). The present study indicates that Act5 and Act11 could be potential biological control of the tested pathogens.